S100A8/A9 aggravates post-ischemic heart failure through activation of RAGE-dependent NF-[kappa]B signaling - Volz, Hans Christian; Laohachewin, Danai; Seidel, Cathrin; Lasitschka, Felix; Keilbach, Kirsten; Wienbrandt, Alexandra; Andrassy, Joachim; Bierhaus, Angelika; Kaya, Ziya; Katus, Hugo; Andrassy, Martin (Basic research in cardiology, 2012)
The extracellular heterodimeric protein S100A8/A9 activates the innate immune system through activation of the receptor of advanced glycation end products (RAGE) and Toll-like receptors. As activation of RAGE has recently been associated with sustained myocardial inflammation and heart failure (HF) we studied the role of S100A8/A9 in the development of post-ischemic HF. Hypoxia led to sustained induction of S100A8/A9 accompanied by increased nuclear factor (NF-)κB binding activity and increased expression of pro-inflammatory cytokines in cardiac fibroblasts and macrophages. Knockdown of either S100A8/A9 or RAGE rescued the induction of pro-inflammatory cytokines and NF-κB activation after hypoxia. In a murine model of post-ischemic HF both cardiac RNA and protein levels of S100A8/A9 were elevated as soon as 30 min after hypoxia with sustained activation up to 28 days after ischemic injury. Treatment with recombinant S100A8/A9 resulted in reduced cardiac performance following ischemia/reperfusion. Chimera experiments after bone marrow transplantation demonstrated the importance of RAGE expression on immune cells for their recruitment to the injured myocardium aggravating post-ischemic heart failure. Signaling studies in isolated ventricles indicated that MAP kinases JNK, ERK1/2 as well as NF-κB mediate signals downstream of S100A8/A9-RAGE in post-ischemic heart failure. Interestingly, cardiac performance was not affected by administration of S100A8/A9 in RAGE−/−-mice, which demonstrated significantly improved cardiac recovery compared to WT-mice. Our study provides evidence that sustained activation of S100A8/A9 critically contributes to the development of post-ischemic HF driving the progressive course of HF through activation of RAGE.
Gesehen am 30.07.2018